Generation of cross-reactive cytotoxic T lymphocytes following immunization of mice with various bluetongue virus types. - Jeggo, M H (1982)
Mice immunized with a single bluetongue (BT) virus type were shown to produce cytotoxic T lymphocytes (CTL's) which cross-reactive with a number of BT virus types. These cross-reactive CTL's could be induced by both primary in vivo and secondary in vitro stimulation. A varying degree of cross-reactivity occurred with the six BT types examined. Aspects of the character of this cross-reactivity were examined and its role in protection from disease and vaccination strategy is discussed.